Germline mutations in 40 cancer susceptibility genes among Chinese patients with high hereditary risk breast cancer. Issue 2 (8th November 2018) - Li, Jun‐Yan; Jing, Ruilin; Wei, Hongyi; Wang, Minghao; Xiaowei, Qi; Liu, Haoxi; Jian, Liu; Ou, Jiang‐Hua; Jiang, Wei‐Hua; Tian, Fu‐Guo; Sheng, Yuan; Li, Heng‐Yu; et al.
Abstract : Multigene panel testing of breast cancer predisposition genes have been extensively conducted in Europe and America, which is relatively rare in Asia however. In this study, we assessed the frequency of germline mutations in 40 cancer predisposition genes, including BRCA1 and BRCA2, among a large cohort of Chinese patients with high hereditary risk of BC. From 2015 to 2016, consecutive BC patients from 26 centers of China with high hereditary risk were recruited (n = 937). Clinical information was collected and next‐generation sequencing (NGS) was performed using blood samples of participants to identify germline mutations. In total, we acquired 223 patients with putative germline mutations, including 159 in BRCA1/2, 61 in 15 other BC susceptibility genes and 3 in both BRCA1/2 and non‐ BRCA1/2 gene. Major mutant non‐ BRCA1/2 genes were TP53 (n = 18), PALB2 (n = 11), CHEK2 (n = 6), ATM (n = 6) and BARD1 (n = 5). No factors predicted pathologic mutations in non‐ BRCA1/2 genes when treated as a whole. TP53 mutations were associated with HER‐2 positive BC and younger age at diagnosis; and CHEK2 and PALB2 mutations were enriched in patients with luminal BC. Among high hereditary risk Chinese BC patients, 23.8% contained germline mutations, including 6.8% in non‐ BRCA1/2 genes. TP53 and PALB2 had a relatively high mutation rate (1.9 and 1.2%). Although no factors predicted for detrimental mutations in non‐ BRCA1/2 genes, some clinical features were associated with mutations of several particular genes. Abstract : What's new? The prevalence of mutations in breast cancer predisposition genesare not well investigated in Asia. We assessed germline mutations of 40 cancer susceptibility genes in 937 consecutive selected breast cancer patients from 26 centers of China, and discovered 23.8% of participates carried the pathogenic mutation, including 6.8% with mutations in non‐ BRCA1/2 genes, while TP53 and PALB2 had a relatively high mutation rates (1.9% and 1.2%).There was no factors predicted for detrimental mutations in non‐ BRCA1/2 genes when treated as a whole.